1985
DOI: 10.1136/hrt.54.4.392
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery ectasia. Its prevalence and clinical significance in 4993 patients.

Abstract: SUMMARY To assess the clinical significance of coronary artery ectasia 4993 consecutive coronary arteriograms were reviewed to identify patients with this condition and to allow the assessment of their progress. Coronary ectasia was a relatively uncommon finding (overall incidence 1-4%). It was not related to the development of aortic aneurysms and did not affect the outcome, results of coronary artery surgery, or symptoms.Coronary artery ectasia has been a well recognised, if uncommon, pathological finding fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
372
4
30

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 441 publications
(421 citation statements)
references
References 14 publications
15
372
4
30
Order By: Relevance
“…Of the four age segments, CAE was more common in the younger age group, while stenotic CAD was common in older age. This is in agreement with previous studies [10][11][12][13]. Giannoglu et al [11] also reported more male patients having CAE.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Of the four age segments, CAE was more common in the younger age group, while stenotic CAD was common in older age. This is in agreement with previous studies [10][11][12][13]. Giannoglu et al [11] also reported more male patients having CAE.…”
Section: Discussionsupporting
confidence: 83%
“…Giannoglu et al [11] also reported more male patients having CAE. This gender difference has been reported previously [12,13] and is supposed to be due to a lower incidence of CAD in women [11]. Considering the different age segments, we found nearly three quarters of CAE to be younger than 60 years .…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…It is characterized by an abnormal dilatation of coronary artery, represents a form of atherosclerotic coronary artery disease, seen in 3-8% of patients undergoing coronary angiography [1]. Abnormal dilatation of a vessel could be long segmental involvement of partial aneurysm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery ectasia (CAE) is a well-recognized but relatively uncommon finding encountered during diagnostic coronary angiography in adult [1]. In infant, coronary dilatation is mostly due to coronary complications of Kawasaki disease (KD).…”
Section: Introductionmentioning
confidence: 99%